2008
DOI: 10.1080/09595230801927372
|View full text |Cite
|
Sign up to set email alerts
|

The principles of agonist pharmacotherapy for psychostimulant dependence

Abstract: Issues. Psychostimulant dependence is a chronic, relapsing condition which is highly treatment refractory. No medications to date have been any more successful than placebo in reducing psychostimulant use in dependent patients. Agonist strategies have attracted limited attention. Approach. Successful examples of agonist pharmacotherapy in the treatment of heroin and nicotine dependence are first considered. Agonist pharmacological approaches to the treatment of psychostimulant dependence are then examined, bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 106 publications
1
22
0
Order By: Relevance
“…This characteristic, together with the present findings that MOD cannot offer any benefits when the individual is already exhausted due to the lack of sleep, strengthens the potential of using MOD as a replacement treatment in patients dependent on other psychostimulant drugs (Dackis et al 2005;Karila et al 2008;Martínez-Raga et al 2008;Shearer 2008).…”
Section: Discussionsupporting
confidence: 77%
“…This characteristic, together with the present findings that MOD cannot offer any benefits when the individual is already exhausted due to the lack of sleep, strengthens the potential of using MOD as a replacement treatment in patients dependent on other psychostimulant drugs (Dackis et al 2005;Karila et al 2008;Martínez-Raga et al 2008;Shearer 2008).…”
Section: Discussionsupporting
confidence: 77%
“…While studies are commonly limited in regards to treatment retention and a predominant focus on short-term effects, there appears to be a trend for tailored and more intensive interventions to result in superior efficacy. This reflects evidence that several systematic reviews focusing on psycho-social treatment measures for stimulant use more generally have found (Dutra et al, 2008;Lee & Rawson, 2008;Shearer, 2008), even though it needs to be considered that these populations may vary in terms of socio-economic, drug use and co-morbidity profiles. As such -and given the current status of pharmaco-therapeutic treatment options (see below) -psychosocial treatment options are likely the best, realistically available treatment option for crack/cocaine abuse currently available.…”
Section: Discussionmentioning
confidence: 89%
“…More recently, studies examining the effects of oral d-amphetamine on methamphetamine abuse have shown that it can reduce craving, withdrawal symptoms and intake (Galloway et al 2010; Longo et al 2009). With the agonist therapy treatment model in mind (Shearer, 2008), these findings have been extended to another addictive psychostimulant, cocaine. In three randomized, double-blind, placebo-controlled clinical trials, cocaine-dependent individuals showed modest but significant decreases in cocaine use relative to placebo after treatment with d-amphetamine (Grabowski et al 2001, 2004; Shearer et al 2003).…”
Section: Introductionmentioning
confidence: 99%